Study of Fishball Chips with the Use of Different Types of Fish and Frying Temperatures on Nutritional Content - Fatmawati, Amilia Dwi; Rosida, Dedin Finatsiyatul (Asia Pacific Network for Sustainable Agriculture, Food and Energy (SAFE-Network), 2025)
Fishball chips are snacks made from processed meatballs that are thinly sliced ??and then fried. This study used types of anchovies, mackerel and tongue and the use of frying temperatures of 70 ° C, 80 ° C, 90 ° C with a vacuum frying method. The use of this vacuum frying method in the processing of processed fish products such as fishball chips is an alternative to produce products that are crispier and lower in oil and are able to maintain the taste and color of the product. The purpose of this study was to determine the effect of fish type and frying temperature on the quality of fishball chips. This study used a Completely Randomized Design (CRD) factorial pattern with two replications. Factor 1 is the type of fish (anchovy, indian mackerel, tongue), factor 2 is the frying temperature with the vacuum frying method (70 ?, 80 ?, 90 ?). Data were analyzed using ANOVA and advanced DMRT tests at the 5% level. The best treatment was indian mackerel type with frying temperature of 80? which produced fish meatball chips with moisture content of 4,07%, ash content of 6,19%, protein content of 32,79%, fat content of 26,80%, and carbohydrate content of 30,14%.